Optimization of the Soft Tissue Envelope of the Nose in Rhinoplasty Utilizing Fat Transfer Combined with Platelet-Rich Fibrin - Kovacevic, Milos; Kosins, Aaron M.; Göksel, Abdülkadir; Riedel, Frank; Bran, Gregor; Veit, Johannes A. (Facial Plastic Surgery, 2021)
A thin or damaged skin soft tissue envelope may cause concerns in primary and secondary rhinoplasty. During postoperative healing, unpredictable scarring and contraction may occur and lead to significant aesthetic and trophic sequelae. Besides a meticulous surgical technique, there are no reliable techniques to prevent long-term skin damage and shrinkage. Fat transfer with addition of platelet-rich fibrin (PRF) harbors the possibility of local soft tissue regeneration and skin rejuvenation through growth factors and mesenchymal stem cells. It may also facilitate the creation of a thin fat layer on the dorsum to prevent shrink-wrap forces and conceal small irregularities. The goal is to provide evidence for the feasibility, durability, and beneficial effect of diced macrofat transfer bonded with PRF on the nasal dorsum. We present the technique of fat transfer conjugated with PRF as a nasal dorsal graft. Clinical endpoints were the prevention of trophic disturbances and atrophy at a 1-year postoperative follow-up. We present the skin mobility test as a clinical indicator of a healthy soft tissue envelope. The presented case series consists of 107 rhinoplasties. Fat was harvested in the umbilical or costal region. PRF was created by centrifugation of autologous whole blood samples. Macrofat was diced, cleaned, and bonded with PRF. The compound transplants were transferred to the nasal dorsum. There were no perioperative complications or wound-healing issues. Mean follow-up was 14 months. Clinical inspection showed good skin quality and no signs of shrinkage, marked scarring, or color changes with positive skin mobility test in all patients. Survival of fat was confirmed by ultrasonography and magnetic resonance imaging. Diced macrofat transfer in conjunction with PRF to the nasal dorsum is a feasible and safe method. A beneficial effect on the soft tissue envelope is demonstrated as well as the prevention of shrink-wrap forces.
Keywords: platelet-rich fibrin; PRF; nasal soft tissue; rhinoplasty; fat transfer